RESEARCH ON THE INFLUENCE OF SYMBIOTIC VALUES ON ALLIANCE PERFORMANCE - Xiao, Jinhua; Han, Shenglong (Chinese Journal of Social Science and Management, 2021)
Artificial intelligence is high-tech industry, and the high research and development costs, the possibility of innovation failure, the international market competition and uncertainty, domestic cross-industry development, and market scuffles and so on, will all cause fatal damage to high-tech enterprises. In this context, creating an AI industrial strategic alliance is the best choice. At this stage, most scholars from the East and the West mainly focus on researching alliance dynamics and the focal enterprises of alliance combination from the perspective of industrial alliance conflicts and collaborations, and they do not think from the perspective of “symbiotic values”. Therefore, this research proposes the research on the impact of symbiotic values on alliance performance. Then, we issued questionnaires to the three provinces and cities of the artificial intelligence industry strategic alliance distributed in northern, central and southern China, and used SPSS22.0 software to examine the questionnaire results with descriptive statistical analysis. The results show that symbiotic beliefs positively affect alliance performance; the communication ability of managerial ability has significant mediating effect on symbiosis belief and alliance performance; customer value has significant moderating effect on management capability and alliance performance.